Pendampingan Tata Cara Wudhu di SDN 1 Jelantik - Shahibul Ardhi; Husaen Sudrajat; Suci Handayani (Jurnal Pengabdian Kepada Masyarakat Al-Amin, 2026)
Ablution (wudhu) is a valid condition for prayer that must be mastered by every Muslim from an early age, yet many elementary school students still lack a proper understanding of its pillars and correct procedure. This community service activity aimed to provide guidance on the correct procedure of ablution for students of SDN 1 Jelantik as an effort to strengthen early worship education. The activity was carried out in April 2026 at the mushala (prayer hall) of SDN 1 Jelantik, involving lower- and upper-grade students in stages. The implementation method combined socialization, demonstration, and direct practice (learning by doing), consisting of four stages: preparation, material socialization, guided practice, and evaluation. The results showed an improvement in students' understanding and skills in reciting the intention, performing the pillars of ablution in the correct order, and reciting the prayer after ablution. Students demonstrated high enthusiasm throughout the mentoring process. This activity is expected to continue through routine habituation at school so that students' awareness of worship becomes stronger and instilled from an early age.